The Moral Failure of the Women in John Ford’s Love’s Sacrifice - Aydoğdu, Merve (Journal of History Culture and Art Research, 2013)
John Ford (1586-1639), who was among the final tragedians of the late English Renaissance, started his career with non-dramatic works and after various dramatic collaborations with Dekker and Heywood, he created three solo tragedies- namely Tis Pity She’s a Whore, the Broken Heart and Love’s Sacrifice- all of which gave clues about the human psychology. Ford employed the themes of love, adultery, desire and death in the afore-mentioned pieces and he always struggled to give his women the freedom their society depraved them of. In Love’s Sacrifice (1633), John Ford produces five women characters all of whom can fearlessly voice their feelings. The typical sixteenth/seventeenth century woman was supposed to be silent and submissive standing only in the domestic sphere allotted to her but Ford’s female characters have been given a certain amount of freedom: the characters to be discussed never hesitate to externalize how they feel or they act in accordance with their wishes. On the one hand, the women can express their desires and Ford seems to favour them. On the other hand, however, he represents them with their defects and all of the women experience moral failure. The aim of this study, thus, is to show the ambivalent attitude of John Ford towards his women. Given the portrayal and consequences of the women’s behaviour, it will be concluded that John Ford was a man of patriarchy and although he seemed to side with his women characters, he promoted the patriarchal order through Love’s Sacrifice.